Plasma membrane of Beta vulgaris storage root shows high water channel activity regulated by cytoplasmic pH and a dual range of calcium concentrations - Alleva, Karina Edith (2006)
Plasma membrane vesicles isolated by two-phase partitioning from the storage root of Beta vulgaris show atypically high water permeability that is equivalent only to those reported for active aquaporins in tonoplast or animal red cells (Pf5542 lm s21 ). The values were determined from the shrinking kinetics measured by stopped-flow light scattering. This high Pf was only partially inhibited by mercury (HgCl2) but showed low activation energy (Ea) consistent with water permeation through water channels. To study short-term regulation of water transport that could be the result of channel gating, the effects of pH, divalent cations, and protection against dephosphorylation were tested. The high Pf observed at pH 8.3 was dramatically reduced by medium acidification. Moreover, intravesicular acidification (corresponding to the cytoplasmic face of the membrane) shut down the aquaporins. De-phosphorylation was discounted as a regulatory mechanism in this preparation. On the other hand, among divalent cations, only calcium showed a clear effect on aquaporin activity, with two distinct ranges of sensitivity to free Ca21 concentration (pCa 8 and pCa 4). Since the normal cytoplasmic free Ca21 sits between these ranges it allows for the possibility of changes in Ca21 to finely up- or down-regulate water channel activity. The calcium effect is predominantly on the cytoplasmic face, and inhibition corresponds to an increase in the activation energy for water transport. In conclusion, these findings establish both cytoplasmic pH and Ca21 as important regulatory factors involved in aquaporin gating.